MICROLEARNING AS A TOOL FOR SCIENTIFIC DISSEMINATION: THERMAL ANALYSIS OF THE PORTUGUESE GOOD LUCK ROOSTER - Magri, Raquel [UNESP]; Gaglieri, Caroline [UNESP]; Alarcon, Rafael Turra [UNESP]; de Souza, Aguinaldo Robinson [UNESP]; Bannach, Gilbert [UNESP] (My University, 2022)
This work aims to produce and disseminate videos that follow the microlearning methodology, to explain the physicochemical properties of cobalt (II) chloride hexahydrate through thermal analysis, and to determine the reliability of the Portuguese good luck rooster. Temporal and social accelerations due to the growth of the technological world are changing the old teaching-learning methodologies; thus, new methods should be explored. In the microlearning methodology, short segments and specific content can be broadcast to anyone at any time. In addition, relating new information to individual’s experiences can favor the teaching-learning process. The good luck rooster is an ornament of Portuguese origin, which can forecast the weather in a limited way, and is composed of cobalt (II) chloride hexahydrate. This compound was characterized by TG-DTA (Simultaneous Thermogravimetry-Differential Thermal Analysis) and DSC (Differential Scanning Calorimetry), verifying that the salt loses its hydration water when exposed to high temperatures, changing its color from pink color to blue.
Keywords: cobalt (II) chloride hexahydrate; microlearning; Thermal Analysis